3.4% Solar‐to‐Ammonia Efficiency from Nitrate Using Fe Single Atomic Catalyst Supported on MoS2 Nanosheets (Adv. Funct. Mater. 18/2022). (2nd May 2022) - Li, Ji; Zhang, Yuan; Liu, Chao; Zheng, Lirong; Petit, Eddy; Qi, Kun; Zhang, Yang; Wu, Huali; Wang, Wensen; Tiberj, Antoine; Wang, Xuechuan; Chhowalla, Manish; et al.
Abstract : Solar‐to‐Ammonia Efficiency In article 2108316, Damien Voiry and co‐workers report a single atom catalyst based on iron single atoms supported on 2D MoS2 nanosheets. The catalyst demonstrates near‐unity selectivity for the electrosynthesis of ammonia with a solar‐to‐NH3 efficiency of 3.4% when coupled to an external InGaP/GaAs/Ge triple‐junction solar cell.